Process equipment analysis integrated gas treatment unit for diethylene glycol absorbent change to triethylene glyco - O. Yu. Manikhin; V. V. Shalay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Based on the calculated data obtained by using the software complex of modeling of technological processes for preparation of hydrocarbon raw materials of the domestic development «GIBBS», the article confirmed the advantage of triethylene glycol relative to diethylene glycol in terms of reduction of dew point temperature of dried gas in changing thermobaric conditions of operation of technological equipment of the complex gas treatment plant. The design parameters are confirmed by experimental data obtained during operation of the natural gas drying system at the facilities of Gazprom dobycha Noyabrsk LLC, where triethylene glycol is used as an absorbent